Self-Directed Learning An imperative for education in a complex society - du Toit-Brits, Charlene (NWU Self-Directed Learning Series, 2021)
This book on self-directed learning (SDL) is devoted to original academic scholarship within the field of education, and is the 6th volume in the North-West University (NWU) SDL book series. In this book the authors explore how self-directed learning can be considered an imperative for education in a complex modern society. Although each chapter represents independent research in the field of self-directed learning, the chapters form a coherent contribution concerning the scholarship of self-directed learning, and specifically the effect of environmental and praxis contexts on the enhancement of self-directed learning in a complex society. The publication as a whole provides diverse perspectives on the importance of self-directed learning in varied contexts. Scholars working in a wide range of fields are drawn together in this scholarly work to present a comprehensive dialogue regarding self-directed learning and how this concept functions in a complex and dynamic higher education context. This book presents a combination of theory and practice, which reflects selected conceptual dimensions of self-directed learning in society, as well as research-based findings pertaining to current topical issues relating to implementing self-directed learning in the modern world. The varied methodologies provide the reader with different and balanced perspectives, as well as varied and innovative ideas on how to conduct research in the field of self-directed learning.